Mimetic Quality: Consumer Quality Conventions and Strategic Mimicry in Food Distribution - Barbera, Filippo; Dagnes, Joselle; Monaco, Roberto Di (The International Journal of Sociology of Agriculture and Food, 2018)
Quality is a key dimension of markets and competition in advanced capitalist societies. While political economy recognizes the role quality plays for consumers’ purchasing strategies, it is less attentive to quality as a contested field where symbolic struggles and strategic manoeuvring take place. We argue that the quality-based strategies of hybrid organizations in food distribution represent a combination of different worlds of quality and judgment devices. This combination defines a camouflage strategy through which conventional food distribution chains such as high-end supermarkets conquer specific zones of the quality space. We thus maintain that the quality strategies of these organizations are explicitly boundary-spanning. To be successful, hybrid organizations need to cover both new and traditional quality conventions, overcoming divisions among different worlds while maintaining a coherent profile. This effort requires a strategy that is able to leverage situation-specific cultural meanings quite independently from individual-level attributes.